Local Effect of Neurotrophin-3 in Neuronal Inflammation of Allergic Rhinitis: Preliminary Report - Onur İsmi; Cengiz Özcan; Yusuf Vayisoğlu; Kemal Görür; Tuba Karabacak; Gürbüz Polat; Taylan Güçlütürk (Balkan Medical Journal, 2015)
Background: Allergic rhinitis is a common inflammatory nasal mucosal disease characterized by sneezing, watery nasal discharge, nasal obstruction and itching. Although allergen-specific antibodies play a main role in the allergic airway inflammation, neuronal inflammation may also contribute to the symptoms of allergic rhinitis. Neuronal inflammation is primarily caused by the stimulation of sensory nerve endings with histamine. It has been shown that neurotrophins may also have a role in allergic reactions and neuronal inflammation. Nerve growth factor, neurotrophin 3 (NT-3), neurotrophin 4/5 and brain-derived neurotrophic factor are members of the neurotrophin family. Although nerve growth factor and brain-derived neurotrophic factor are well studied in allergic rhinitis patients, the exact role of Neurotrophin-3 is not known.